Question:

How to integrate x(sinx)^2 ?

by  |  earlier

0 LIKES UnLike

Please tell me How to integrate x(sinx)^2

 Tags:

   Report

5 ANSWERS


  1. ∫x sin²(x)dx

    Let u = x

    du = dx

    Let dv = sin²(x) dx

    v =  ÃƒÂ¢Ã‚ˆÂ«sin²(x) dx  = (1/2)∫dx - (1/2)∫cos(2x)dx = x/2 - sin(2x)/4 + c

    v = x/2 - sin(2x)/4 + c

    ∫udv = uv - ∫vdu

    ∫x sin²(x)dx  = x(x/2 - sin(2x)/4) - ∫(x/2 - sin(2x)/4)dx + c

    ∫x sin²(x)dx  =  x²/2 - xsin(2x)/4 - x²/4 + 1/4∫sin(2x)dx + c

    ∫x sin²(x)dx  =  x²/2 - xsin(2x)/4 + x²/4 + 1/4(-cos(2x)/2) + c

    ∫x sin²(x)dx  = x²/4 - xsin(2x)/4  - cos(2x)/8 + c


  2. ∫ (  x sin^2(x) dx )

    First, use the half angle identity

    sin^2(x) = (1/2)(1 - cos(2x))

    ∫ (  x (1/2) (1 - cos(2x))  dx )

    Factor out the constant (1/2) from the integral.

    (1/2) ∫ (  x (1 - cos(2x)) dx )

    Distribute the x, to get

    (1/2) ∫ ( [ x - x cos(2x) ] dx )

    We can split this into two integrals, to get

    (1/2) [ ∫ ( x dx ) - ∫ (  x cos(2x) dx ) ]

    (1/2) [ (1/2)x^2  -  Ã¢ÂˆÂ« ( x cos(2x) dx ) ]

    Distribute the (1/2), to get

    (1/4) x^2 - (1/2) ∫ (  x cos(2x) dx )

    From here, we can use integration by parts.

    Let u = x.  dv = cos(2x) dx.

    du = dx.  v = (1/2) sin(2x)

    Apply the integration by parts, to get

    (1/4) x^2 - (1/2) [ (1/2)x sin(2x) - ∫ ( (1/2)sin(2x) dx ) ]

    Distribute the (1/2), to get

    (1/4) x^2 - (1/4) x sin(2x) + (1/2) ∫ (  (1/2) sin(2x) dx )

    And now, factor the (1/2) from the remaining integral.  This merges with the other (1/2) to make (1/4).

    (1/4) x^2 - (1/4) x sin(2x) + (1/4) ∫( sin(2x) dx )

    Which is now an easy integral, as the integral of sin(2x) is equal to (-1/2)cos(2x).

    (1/4) x^2 - (1/4) x sin(2x) + (1/4) (-1/2) cos(2x) + C

    Simplify,

    (1/4) x^2 - (1/4) x sin(2x) - (1/8)cos(2x) + C

  3. ∫x sin^2 x dx=

    ∫x(1-cos 2x)/2 dx=

    1/2∫x dx - 1/2∫x cos 2x dx=

    (1/2)x - 1/8∫(2x) cos(2x) d(2x)

    FRom here y=2x and computing

    ∫y cos y dy by parts

    ∫y cos y dy=

    ∫y d sin y= y sin y - ∫sin y dy=

    ysin y +cos y +C

    Substitute back and OK


  4. by using LATE rule

  5. ∫sin²x dx

    = (1/2) ∫2sin²x dx

    = (1/2) ∫(1 - cos 2x) dx

    = x/2 - (1/4)sin 2x ...   (1)

    (Cont. of integration is not shown as the result is to be used later.)

    ∫xsin²x dx

    = x ∫sin²x dx - ∫[d/dx(x) ∫sin²x dx] dx

    = x[x/2 - (1/4)sin 2x] - ∫[x/2 - (1/4)sin 2x] dx   [using result (1)]

    =  x²/2 - (x/4)sin 2x - x²/4 - (1/8)cos 2x + c

    = x²/4 - (x/4)sin 2x - (1/8)cos 2x + c

Question Stats

Latest activity: earlier.
This question has 5 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.